Navigating the threshold of student–staff partnerships: a case study from an Ontario teaching and learning institute. Issue 1 (2nd January 2016) - Marquis, Elizabeth; Puri, Varun; Wan, Stephanie; Ahmad, Arshad; Goff, Lori; Knorr, Kris; Vassileva, Ianitza; Woo, Jason
Abstract: This article presents the results of research that examined the experiences of staff and students engaged in a novel 'student scholars' program established through a university teaching and learning institute in Ontario, Canada. Drawing from participant reflections and focus group data, we describe the benefits and challenges perceived by individuals partnering through this initiative, using the theoretical framework of threshold concepts to understand these experiences. We describe ways in which participants experienced partnering as both troublesome and – in some cases – transformative, and consider the implications of these findings for academic developers engaging in and/or supporting faculty with the process of partnering with students.